Integrating telerehabilitation and serious gaming during home-based exercise intervention after stroke: A randomized controlled pilot trial of the DISKO-tool - Elisabet Åkesson; Maria Bergqvist; Maja Eder; Nanna Bäckström; Erika Franzén; Jörgen Borg; Susanne Palmcrantz (Digital Health)
Background To support recovery after stroke, rehabilitative actions and innovations are needed in resource-limited health care and geographically distant regions. Objective The first objective was to explore the feasibility of performing home-based training using the novel DISKO-tool including both telerehabilitation and serious gaming customized to target dynamic balance poststroke. The second objective was to assess the outcome using the Balance Evaluation Systems Test as the primary outcome. Methods This randomized controlled pilot trial, included ambulatory patients ≥18 years of age with physical impairments 3–6 months poststroke. During primary care rehabilitation, patients were randomized to conventional and 6 weeks of DISKO-tool training in the home ( n  = 10) or conventional training only ( n  = 11). Feasibility was assessed with process, resource, management, and scientific perspectives using questionnaires, logbooks, DISKO-tool data and clinical assessments. Results The study design was feasible including safety, resource capacity, a retention rate of 87%, high compliance to the protocol (mean 30 training days), and highly rated experience of the tool (median 10 of 10) despite some technical issues. The recruitment rate was low. The DISKO-group presented improved balance, especially in anticipatory postural adjustment compared to the conventional group ( p  < 0.001; effect size 2.195; 95% CI 1.015–3.336). Conclusions Applying the DISKO-tool in home-based stroke rehabilitation was feasible and the piloted methodology suited for a larger RCT, as long as a wider inclusion time window poststroke is applied to enhance the recruitment rate. Rapid development and a limited lifespan of off-the-shelf hardware products warrant continuous technical development.